Religious tourism in Mongolia and opport unities for its development - Borbandi, Munkhtsatsralt; Sharaa, Dogmiichoidon (Studia Philosophiae Et Juris, 2023)
Religious tourism is a growing branch of tourism and religious studies. In this study, we have considered how researchers have studies religious tourism in our country. In the future, religious tourism can be developed based on the experience of other countries about the resources and opportunities for independent development, as well as the rich history, culture, archaeological finds, temples and natural beauty that have been passed down to us through the religion of God, temples, ruins of temples, museums, and it was told about the possibility of observing the presence of pictures, sculptures, castings, appliques, and objects as a means of religious tourism and a route with a specific purpose. It is also possible to attract the interest of travelers and tourists by explaining that all things, including temples and shrines, have their symbols, customs and meanings in the context of religious tourism. This year, due to historical events such as the appointment of X Bogda Jawzandamba and the change of abbot of Gandantekechenlin Monastery, the Mongolian God Religious Center, we tried to put forward our suggestions on the possibility of developing the Mongolian Traditional Religion of Gods as a center for god worshipers, religious tourism and pilgrimage. Монгол Улс дахь шашны аялал жуулчлал, хөгжүүлэх боломж Хураангуй Аялал жуулчлал, шашин судлалын салбарт хавсарга асуудал мэт хоцорч байгаа сэдэв бол шашны аялал жуулчлал билээ. Бид энэхүү өгүүлэлдээ манай улсад шашны аялал жуулчлалыг судлаачид хэрхэн авч үзэж байгааг тоймлохыг зорилоо. Мөн цаашид шашны аялал жуулчлалыг бие даасан салбар болгон хөгжүүлэх нөөц боломжийг зарим орны туршлага жишээнд үндэслэн хөгжүүлж болох тухай, тэрчлэн бидэнд бурхны шашнаар дамжин өвлөж ирсэн арвин түүх, соёл, археологийн олдвор, сүм хийд хийгээд байгалийн үзэсгэлэнтэй хосолмол байдлаар орших сүм хийд, сүм хийдийн туурь, музей, уран зураг, уран баримал, цутгамал, наамал, хөөмөл байгааг шашны аялал жуулчлалын бүтээгдэхүүн, тодорхой зорилготой маршрут болгож ашиглах боломжийн тухай өгүүлэв. Мөн бурхны шашны сүм хийд орон тэргүүтэй бүхий л эд зүйл нь угтаа бэлгэдэл, ёс, утга агуулгатай байдгийг шашны аялал жуулчлалын хүрээнд домогчлон, түүхчлэн тайлбарласнаар аялагч, жуулчдын сонирхлыг татах боломжтой юм. Энэ онд X Богд Жавзандамба тодорсон, Монголын Бурхан Шашинтны Төв Гандантэгчэнлин хийдийн тэргүүн хамба лам солигдсон зэрэг түүхэн үйл явдлууд тохиолдсонтой холбоотойгоор цаашид монголын уламжлалт бурхны шашин нь бурхны шашинтны төв, шашны аялал жуулчлал, эргэл мөргөлийн төв болон хөгжих боломжийн тухай өөрсдийн саналаа дэвшүүлэхийг хичээв. Tүлхүүр үгс: аялал жуулчлал, шашны аялал жуулчлал, бурхны шашин буддын шашин